Total Synthesis of Aspidosperma and Strychnos Alkaloids through Indole Dearomatization. Issue 38 (16th May 2019) - Saya, Jordy M.; Ruijter, Eelco; Orru, Romano V. A.
Abstract: Monoterpenoid indole alkaloids are the major class of tryptamine‐derived alkaloids found in nature. Together with their structural complexity, this has attracted great interest from synthetic organic chemists. In this Review, the syntheses of Aspidosperma and Strychnos alkaloids through dearomatization of indoles are discussed. Abstract : Dearomatization strategy : Aspidosperma ‐ and Strychnos ‐type alkaloids have been attractive targets for natural product synthesis due to their challenging structures. Inspired by nature, many dearomatization strategies have been reported over the past seven decades. Nevertheless, this field has maintained substantial interest and, therefore, it is important to provide a comprehensive historical perspective, which presents an essential guideline for the future of this field.